IL-1 Family Members in Cancer; Two Sides to Every Story - Baker, Kevin J.; Houston, Aileen; Brint, Elizabeth (Frontiers in Immunology, 2019)
The IL-1 family of cytokines currently comprises of seven ligands with pro-inflammatory activity (IL-1α and IL-1β, IL-18, IL-33, IL-36α, IL-36β, IL-36γ) as well as two ligands with anti-inflammatory activity (IL-37, IL-38). These cytokines are known to play a key role in modulating both the innate and adaptive immunes response, with dysregulation linked to a variety of autoimmune and inflammatory diseases. Given the increasing appreciation of the link between inflammation and cancer, the role of several members of this family in the pathogenesis of cancer has been extensively investigated. In this review, we highlight both the pro- and anti-tumorigenic effects identified for almost all members of this family, and explore potential underlying mechanisms accounting for these divergent effects. Such dual functions need to be carefully assessed when developing therapeutic intervention strategies targeting these cytokines in cancer.